Vitamin C and endogenous cortisol in foreign‑body inflammatory response in pacus - Belo, Marco Antonio de Andrade; Moraes, Julieta Rodini Engrácia de; Soares, Vando Edésio; Martins, Maurício Laterça; Brum, Camila Dantas; Moraes, Flávio Ruas de (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate the effect of food supplementation with vitamin C on macrophage and multinucleated giant cell (MGC) activities of pacus at two stocking densities. The experiment was carried out in a 2x2x3 split-plot factorial arrangement with: 0 and 500 mg kg‑1 vitamin C; 5 and 20 kg m‑3 stocking densities; and evaluation times at 3, 6, and 12 days after the subcutaneous implantation of glass coverslips (DPI). The number of macrophages and MGC, as well as cortisol and glucose plasma levels were determined. The number of macrophages and MGC with two to five nuclei was significantly greater in fish supplemented with vitamin C at 5 kg m‑3 stocking density at 3 DPI in comparison to nonsupplemented ones. The macrophage and MGC counts were lower in fish with high‑plasma cortisol concentration. Supplementation with 500 mg vitamin C benefits macrophage activity on foreign‑body inflammation, and high‑cortisol concentration has suppressive effects on this response.